"What Do You Want to Learn or Work on Today?": Benefits and Barriers to Asking Residents for Self‐identified Learning Goals. Issue 3 (14th December 2020) - Fazzio, Pamela; Hardy, Emily; Chamberlain, Meghan; Genecin, Isabel; Weiss, Anna; Posner, Jill; Shatzer, John; Shaw, Kathy
Abstract: Background: In the emergency department (ED), residents and attendings may have a short‐term relationship, such as a single shift. This poses challenges to learner assessment, instructional strategy selection, and provision of substantive feedback. We implemented a process for residents to identify goals for ED shifts; characterized residents' goals; and determined how goal identification affected learning, teaching, and feedback. Methods: This was an observational study in a large, tertiary pediatric ED using mixed methods. Residents were asked to identify learning goals for each shift and were asked postshift if they had identified, accomplished, and/or received feedback on these goals. Goals were categorized by Accreditation Council for Graduate Medical Education Core Competencies. Predictors of goal identification, accomplishment, and receipt of feedback were determined. Residents and attendings were interviewed about their experiences. Results: We collected 306 end‐of‐shift surveys (74% response rate) and 358 goals and conducted 29 interviews. We found that: 1) Goal setting facilitated perceived learning. Residents identified goals 54% of the time. They accomplished 89% of and received feedback on 76% of goals. 2) Residents' perceived weaknesses, future practice settings, and available patients informed their goals. Most goals mapped to patient care (59%) or medical knowledge (37%) competencies. 3) Goal identification helped attendings determine residents' needs. 4) Ideal goals were specific and achievable. 5) Common barriers were busyness of the ED and difficulty creating goals. Residents were less likely to identify goals (odds ratio [OR] = 0.62, 95% confidence interval [CI] = 0.41 to 0.94) and receive feedback on busy evening shifts (OR = 0.19, 95% CI = 0.10 to 0.37) and were most likely to receive feedback overnight (OR = 3.66, 95% CI = 1.87 to 7.14). Conclusions: Asking residents to identify goals for ED shifts as an instructional strategy facilitated perceived learning, goal accomplishment, and receipt of feedback. Resident‐driven goal identification is a simple and effective instructional strategy that physicians can incorporate into their precepting in the ED.